Good and Bad Corporate Social Responsibility in Islamic Business Ethics Perspective - Triwibowo, Ananto; Baidhowi, Muhammad Mujib; Sugeng, Anggoro (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2023)
Abstract This research aims to analyze good and bad corporate social responsibility practices when viewed with Islamic business ethics. The method used is a qualitative method with a grounded theory approach using secondary data sources where the source comes from several examples of company cases in Indonesia which are then reviewed with literature on Islamic business ethics in particular and Islamic economics in general. The results of the study concluded that the application of business social responsibility that is less professional actually has a negative impact on the company itself. One example of violations that occur in the application of corporate social responsibility is the practice of corruption and policies that only provide benefits for certain groups. In Islamic business ethics, the implementation of good corporate social responsibility can refer to the maqasid sharia principle, namely with the aim of protecting religion, soul, mind, property, and lineage